Spectrophotometric Methods for Simultaneous Estimation of Mefenamic Acid and Tizanidine in Tablets - KUMAR, ASHOK; PANGHAL, SURENDER; MALLAPUR, SUDHA; KUMAR, RAMESH; SINGH, AVANISH (Asian Journal of Chemistry, 2010)
Two spectrophotometric methods namely Vierordt's method and Q-analysis based on the derivation of the main spectra have been developed for the simultaneous analysis of mefenamic acid and tizanidine in a tablet formulation without involving any prior separation or masking. In Vierordt's method, the drugs were determined by using the absorptivity values of mefenamic acid and tizanidine at selected wavelengths, viz., 216.8 and 234.3 nm, respectively. In Q-analysis method, isoabsorptive point was found to be at 224.6 nm. Both the drugs obey Beer's law in concentration range of 4-18 μg/mL (mefenamic acid) and 4-24 μg/mL (tizanidine). The results obtained were compared statistically by Student t-test and by the variance ratio F-test with those obtained by each method. Both the methods were found to be simple, rapid and accurate and can be adopted in routine analysis of drugs in formulations.